Heat Transfer Augmentation of Al2O3 Nanofluid in 60:40 Water to Ethylene Glycol Mixture. (November 2015) - Usri, N.A.; Azmi, W.H.; Mamat, Rizalman; Hamid, K. Abdul; Najafi, G.
Abstract: Convectional coolant plays an important part in removing excess heat generated by automotive component to avoid damage and failure of the system. Through recent studies, nanoparticles suspended in base fluid or known as nanofluid have positive effect heat transfer performance. This paper presents the effect of increment of Alumina nanoparticles dispersed in 60:40 water to ethylene glycol based nanofluids towards heat transfer enhancement. For this purpose, nanofluids are prepared using Aluminium Oxide (Al2 O3 ) with average diameter of 13 nm suspended in 60:40 of water to ethylene glycol by volume percentage. The nanofluid is synthesized using two step method and homogenized to lengthen the suspension for volume concentration of 0.2%, 0.4% and 0.6%. The force convection investigation was conducted at a constant heat flux with Reynolds number of less than 20, 000 at a constant working temperature of 50 ̊C. The heat transfer coefficient of nanofluids is compared with the base fluid. It was observed that as the loading of nanoparticles suspended in the base fluid is increased, heat transfer coefficient is also higher. The heat transfer augmentation of Al2 O3 nanofluid at 0.6% volume concentration is higher than 0.2% and 0.4% concentrations.